Is Government Ownership of Banks Really Harmful to Growth? - Svetlana Andrianova; Panicos Demetriades; Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
We put forward a modern version of the 'developmental' view of government-owned banks which shows that the combination of information asymmetries and weak institutions creates scope for such banks to play a growth-promoting role. We present new cross-country evidence consistent with our theoretical predictions. Specifically, we show that during 1995-2007 government ownership of banks has been robustly associated with higher long run growth rates. Moreover, we show that previous results suggesting that government ownership of banks is associated with lower long run growth rates are not robust to conditioning on more 'fundamental' determinants of economic growth.
Keywords: O16; G18; G28; K42; 330; Public banks; economic growth; quality of governance; regulation